2017
DOI: 10.1016/j.cej.2017.02.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sepiolite bed material on gas composition and tar mitigation during C. cardunculus L. gasification

Abstract: Sepiolite, a clay mineral that is commonly used as adsorbent, is proposed as bed material for biomass gasification in a lab-scale bubbling fluidized bed. In order to compare the obtained gas composition and tar generation, silica sand has been used as reference bed material. C. cardunculus L. has been employed as biomass feedstock. The operating temperature is varied from 830 to 875°C, at constant equivalence ratio (ER) of 0.30. The gas produced with sepiolite as bed material has a slightly lower quality than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The ratios of all the gaseous components exhibited a decreasing trend over CL, which was due to high concentration of CO 2 and CH 4 in the syngas. However, H 2 /CO ratio was increased over CL by demonstrating that water‐gas shift reaction dominates at higher CL .…”
Section: Resultsmentioning
confidence: 99%
“…The ratios of all the gaseous components exhibited a decreasing trend over CL, which was due to high concentration of CO 2 and CH 4 in the syngas. However, H 2 /CO ratio was increased over CL by demonstrating that water‐gas shift reaction dominates at higher CL .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reactor content can simply be discharged by heating up the section where the discharge pipe is located. Biomass is top fed by an automatic vibrating system as described in [32]. Nitrogen is introduced through a long pipe stretching to the bottom of the reactor.…”
Section: Experimental Facilitymentioning
confidence: 99%
“…A constant helium flow of 1.2 ml/min is passed through a non-polar VF-5MS capillary column (30 m × 0.25 mm, 0.25 μm film thickness). Additional details with regards to the analysis of the condensable fraction can be found in [32]. The most abundant bio-oil compounds are identified using the NIST 2.0 library.…”
Section: Sampling and Analysis Of Pyrolysis Productsmentioning
confidence: 99%
“…However, the reduction of the content of tars might also be caused by a sorbent and/or catalytic effect of the sepiolite particles [29], which could absorb partially the tars generated or catalyze reactions that promote their cracking. This sorption and catalytic effect of the sepiolite particles will be discussed in the next subsection, where long-term gasification tests conducted in the sepiolite bed are analyzed.…”
Section: Tars and Water Contentsmentioning
confidence: 99%
“…wet impregnation of calcined olivine with nickel nitrate [18] and loading with active metals, such as Fe, Ni, Co, Ce, etc [23]. In the case of sepiolite, different studies have proven the tar sorption and tar cracking reactions induced by this material during biomass pyrolysis and gasification processes [24][25][26][27][28][29]. Serrano et al [29] found an increase of the performance of a bubbling fluidized bed air gasifier working with lignocellulosic biomass when using sepiolite instead of silica sand as bed material, due to the tar reduction and mitigation of agglomeration problems in the sepiolite bed.…”
Section: Introductionmentioning
confidence: 99%